Protest and Pilgrimage in Santiago de Chile. the Case of the Animita of Mauricio Fredes During the Chilean Revolt [Protestar E Peregrinar Em Santiago Do Chile. O Caso Da Animita de Mauricio Fredes Durante a Virada Chilena] [Protestar y Peregrinar en Santiago de Chile. el Caso de la Animita de Mauricio Fredes Durante la Revuelta Chilena] - Urzua-Martinez, S (Universidad de los Andes, Bogota Colombia, 2022)
Animitas are artifacts of a popular religious practice present in Chile and other parts of the Andean world. They are built where someone meets death, far from home and the company of their loved ones. They are generally associated with tragic, bloody or violent deaths, as happened in Santiago de Chile during the social revolt with Mauricio Fredes, a young demonstrator who died in the center of the capital as a result of police repression. The animita of Mauricio Fredes was built and experienced a rapid growth thanks to hundreds of people who came day after day to greet, sing, offer an object or food, or just to observe in silent contemplation. Based on the animita of Mauricio Fredes, we ask ourselves whether these popular cenotaphs are mere mortuary images intended to demarcate the site of a person’s death or whether they are experienced —by their makers and practitioners— as a living and present body. Based on an ethnographic approach, we analyze the animita of Mauricio Fredes, considering the materiality, spatiality, and corporeality of this popular-religious practice. We conclude that these cenotaphs are experienced by their makers and practitioners as a living body, whose growth and development is based on the reciprocal belief of its devotees. We also note that, although it is not typical of the animitas to oppose institutions, the image of Mauricio Fredes became an uncomfortable image, because it provided a physical presence to a victim of a “wrong death” perpetrated by agents of the State. It, therefore, highlighted the strength of this popular religious practice in Chile, which allowed the animita of Mauricio Fredes to grow and persist despite the destructive forces that systematically attacked it. © 2022, Universidad de los Andes, Bogota Colombia. All rights reserved.